Calcium sensing receptor suppresses human pancreatic tumorigenesis through a novel NCX1/Ca2+/β-catenin signaling pathway. Issue 1 (10th July 2016) - Tang, Bo; Chow, Jimmy Y.C.; Dong, Tobias Xiao; Yang, Shi-Ming; Lu, De-Sheng; Carethers, John M.; Dong, Hui
Highlights: The expression level of CaSR is downregulated in pancreatic cancer (PC) tissues. CaSR activation significantly inhibits the proliferation of PC cells both in vitro and in vivo. CaSR activation induces [Ca 2+ ]cyt signaling through NCX1-mediated Ca 2+ entry. CaSR suppresses pancreatic cancer growth via the NCX1/Ca 2+ /β-catenin signaling pathway. Abstract: The calcium sensing receptor (CaSR) is functionally expressed in normal human pancreases, but its pathological role in pancreatic tumorigenesis is currently unknown. We sought to investigate the role of CaSR in pancreatic cancer (PC) and the underlying molecular mechanisms. We revealed that the expression of CaSR was consistently downregulated in the primary cancer tissues from PC patients, which was correlated with tumor size, differentiation and poor survival of the patients. CaSR activation markedly suppressed pancreatic tumorigenesis in vitro and in vivo likely through the Ca 2+ entry mode of Na + /Ca 2+ exchanger 1 (NCX1) to induce Ca 2+ entry into PC cells. Moreover, NCX1-mediated Ca 2+ entry resulted in Ca 2+ -dependent inhibition of β-catenin signaling in PC cells, eventually leading to the inhibition of pancreatic tumorigenesis. Collectively, we demonstrate for the first time that CaSR exerts a suppressive function in pancreatic tumorigenesis through a novel NCX1/Ca 2+ /β-catenin signaling pathway. Targeting this specific signaling pathway could be a potential therapeutic strategy for PC.